Two new species of Tipula (Vestiplex) Bezzi (Diptera, Tipulidae) from Northwest China - Ren, Jinlong; Li, Yan; Yang, Ding (Zootaxa, 2021)
Fourteen species/subspecies of the subgenus Tipula (Vestiplex) Bezzi (1924) were previously known to occur in the Northwest China. Here, four species are added to the fauna of this region. Among them T. (V.) quadricorna sp. nov. and T. (V.) shaanxiana sp. nov. are described and illustrated as new; T. (V.) coquillettiana Alexander, 1924 and T. (V.) scripta Meigen, 1830 are reported from China for the first time. Furthermore, we re-described and illustrated the T. (V.) kuwayamai Alexander, 1921 based on additional morphological characters. A key to the species of Tipula (Vestiplex) from Northwest China is presented.